2015
DOI: 10.1038/srep07896
|View full text |Cite
|
Sign up to set email alerts
|

Mapping sites of aspirin-induced acetylations in live cells by quantitative acid-cleavable activity-based protein profiling (QA-ABPP)

Abstract: Target-identification and understanding of mechanism-of-action (MOA) are challenging for development of small-molecule probes and their application in biology and drug discovery. For example, although aspirin has been widely used for more than 100 years, its molecular targets have not been fully characterized. To cope with this challenge, we developed a novel technique called quantitative acid-cleavable activity-based protein profiling (QA-ABPP) with combination of the following two parts: (i) activity-based p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(82 citation statements)
references
References 55 publications
(66 reference statements)
3
78
0
1
Order By: Relevance
“…Aspirin contains acetyl and salicylate groups both of which have their own targets, and are believed to contribute to its chemopreventive actions. Studies from our laboratory [12-14, 17], and others [15, 16] showed that, besides COX, it can acetylate numerous other proteins. While the identification of the aspirin-mediated acetylation targets has recently gained momentum [15, 16] after our initial reports [12] [14], identification of direct binding targets for salicylic acid has been under-explored [13].…”
Section: Discussionmentioning
confidence: 99%
“…Aspirin contains acetyl and salicylate groups both of which have their own targets, and are believed to contribute to its chemopreventive actions. Studies from our laboratory [12-14, 17], and others [15, 16] showed that, besides COX, it can acetylate numerous other proteins. While the identification of the aspirin-mediated acetylation targets has recently gained momentum [15, 16] after our initial reports [12] [14], identification of direct binding targets for salicylic acid has been under-explored [13].…”
Section: Discussionmentioning
confidence: 99%
“…An iTRAQ quantitative proteomics approach was used in tandem with BONCAT to differentiate any potential background contamination from selective enrichment, 29,30 to enhance the reliability of the results obtained. The background contamination includes the pre-existing proteins nonspecifically binding to the beads, as well as the endogenously biotinylated proteins, since streptavidin beads were used for the protein enrichment.…”
Section: Discussionmentioning
confidence: 99%
“…The iTRAQ labeling technique 29,30,48 was employed to investigate the changes in the proteomic profiles upon autophagy induction, per the manufacturer's instructions with minor modifications. Briefly, the dried digested peptides were resuspended in equal amounts of dissolution buffer (0.5 M TEAB; Sigma-Aldrich, T7408).…”
Section: Isobaric Tag For Relative and Absolute Quantification (Itraqmentioning
confidence: 99%
See 2 more Smart Citations